Oral care and protocols in cancer patients - Bugshan, Waleed Mohammed; Alissa, Abdulrahman Saleh; Baidas, Raghad Ammar; Qwizany, Rawan Rashood Al; Alharbi, Asail Jazi; Alsharif, Abdulrhman Mustafa; Jafer, Alhassen Abdurabuh; Albaz, Abdullah Khalid; Alkhalid, Saud Khalid; Alsultan, Firas Mohammed; Alamoudi, Rawan Mohammed (International Journal Of Community Medicine And Public Health, 2022)
With the passage of time and new emerging techniques significant progression is seen in cancer treatment modalities. However, oral care of the cancer patients is of utmost importance since chemotherapy notably impacts the oral health of cancer patient’s majorly causing mucositis and various other infections. Oral problems are more common in cancer patients, and 80% of patients suffer from them. These oral problems have a profound effect on a patient's ability to eat, drink, and speak and are often accompanied by pain, which can lead to increased demand for systemic drugs, longer hospital stays, and an increased risk of life-threatening system infections. The aim of this research is to review the available information about the oral care and protocols in cancer patients. The dentist's role in the integrated care of oncology patient includes ongoing involvement from diagnosis to end. Various protocols are advised in literature which include the use of dental floss and mouthwash, prior to chemotherapy in oral hygiene procedures, requirement of comprehensive clinical and radiographic examinations when assessing oral health, antibiotic prophylaxis, extractions and certain other protocols. Basic oral care which refers to actions that should be included in a general patient care throughout cancer treatment to maintain good oral health and reduce the risk of local inflammation and infection, is essential for cancer patients. However, future clinical and comprehensive research into oral care protocols among cancer patients could further strengthen the literature and highlight the role of the dentist in this regard.